From Gold to Gaze: The Gendered Lens of Body Shaming in Online Media Coverage of Female Athletes - Rumaysha Gikha Nisrina; Raja Bintang Abrori (Jurnal Sosial Humaniora, 2024)
This study examines the construction of gender identity in online mediacoverage, focusing on the issue of body shaming directed at female athletes.The case of Indonesian weightlifter Nurul Akmal, who experienced bodyshaming after her participation in the 2020 Tokyo Olympics, is analysedusing Alan McKee’s text analysis method, a descriptive qualitative approach,and a constructivist paradigm. News articles from eight prominentIndonesian online media outlets — CNNIndonesia.com, Kompas.com,Tempo.co, Detik.com, Republika.co.id, Liputan6.com, and Okezone.com —were selected as the primary data sources. The findings reveal that onlinemedia frequently frame negative commentary on female athletes' physicalappearance as innocuous humour or mere jest. Furthermore, the portrayal offemale athletes as passive or powerless reinforces their subordinate statuswithin the patriarchal structure, limiting their ability to resist or challengesuch derogatory narratives. This media construction not only perpetuatesgender stereotypes but also undermines efforts to promote gender equalitywithin the realm of sports. The study highlights the need for more critical andgender-sensitive reporting practices to counteract these harmfulrepresentations.